In Vitro and In Vivo Characterization of a Murine Cytomegalovirus with a Transposon Insertional Mutation at Open Reading Frame M43 - Xiao, Jianqiao (American Society for Microbiology, 2000)
We have recently generated a pool of murine cytomegalovirus (MCMV) mutants by using a Tn3-based transposon mutagenesis approach. In this study, one of the MCMV mutants, RvM43, which contained the transposon inserted in open reading frame M43, was characterized. Our results provide the first direct evidence to suggest that M43 is not essential for viral replication in vitro in NIH 3T3 cells. Moreover, RvM43 exhibited a titer similar to that of the wild-type virus in the lungs, livers, spleens, and kidneys of both BALB/c and SCID mice and was as virulent as the wild-type virus in killing SCID mice that had been intraperitoneally infected with the viruses. In contrast, titers of the mutant virus in the salivary glands of the infected animals at 21 days postinfection were significantly (100 to 1,000-fold) lower than those of the wild-type virus and a rescued virus that restored the M43 region and its expression. Thus, M43 appears to be not essential for viral growth in vivo in the lungs, livers, spleens, and kidneys of infected animals and is also dispensable for virulence in killing SCID mice. Moreover, our results suggest that M43 is an MCMV determinant for growth in the salivary glands. Studies of viral genes required for replication in the salivary glands are important in understanding the mechanism of viral tropism for the salivary glands and shedding in saliva, which is believed to be one of the major routes of CMV transmission among healthy human populations.